2011
DOI: 10.1152/jn.00729.2010
|View full text |Cite
|
Sign up to set email alerts
|

Distinct maturation profiles of perisomatic and dendritic targeting GABAergic interneurons in the mouse primary visual cortex during the critical period of ocular dominance plasticity

Abstract: Lazarus MS, Huang ZJ. Distinct maturation profiles of perisomatic and dendritic targeting GABAergic interneurons in the mouse primary visual cortex during the critical period of ocular dominance plasticity. J Neurophysiol 106: 775-787, 2011. First published May 25, 2011 doi:10.1152/jn.00729.2010In the rodent primary visual cortex, maturation of GABA inhibitory circuitry is regulated by visual input and contributes to the onset and progression of ocular dominance (OD) plasticity. Cortical inhibitory circuitry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 70 publications
5
68
1
Order By: Relevance
“…Together, these results suggest increased presynaptic vesicles and/or GABA loading, especially in PV interneurons, in MeCP2 −/y V1. During the critical period of visual cortical development (25), which spans around 3 wk after eye opening, GABA + PV interneurons undergo substantial maturation in synaptic innervation and physiological properties, concomitant with increased expression and synaptic localization of GAD67, GAD65, and PV (18,24,26). In V1 of MeCP2 −/y mice, we found that increased expression of GAD67, GAD65, vGAT, and PV persisted to at least the fifth week ( Fig.…”
Section: Accelerated Maturation Of Parvalbumin Interneuron Network Inmentioning
confidence: 66%
See 2 more Smart Citations
“…Together, these results suggest increased presynaptic vesicles and/or GABA loading, especially in PV interneurons, in MeCP2 −/y V1. During the critical period of visual cortical development (25), which spans around 3 wk after eye opening, GABA + PV interneurons undergo substantial maturation in synaptic innervation and physiological properties, concomitant with increased expression and synaptic localization of GAD67, GAD65, and PV (18,24,26). In V1 of MeCP2 −/y mice, we found that increased expression of GAD67, GAD65, vGAT, and PV persisted to at least the fifth week ( Fig.…”
Section: Accelerated Maturation Of Parvalbumin Interneuron Network Inmentioning
confidence: 66%
“…It should be noted that, in addition to mediating cytosolic GABA synthesis, which influences cellular GABA levels, GAD67 and GAD65 form complexes that directly interact with vGAT on synaptic vesicles, thereby facilitating the coupling from GABA synthesis to vesicular packaging (51,52). The key role of GAD67, GAD65, PV, and vGAT in regulating vesicular GABA content and release (26,(51)(52)(53) suggest that alterations in their levels may impact the strength and/or dynamics of GABA transmission (54), especially during fast spiking in PV cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, there is evidence that the rate-limiting enzyme for GABA synthesis (GAD67) is reduced in the cortex of individuals with bipolar disorder (Thompson et al, 2009) and hippocampus of depressed individuals (Thompson et al, 2011). Although robust changes in cortical GAD67 mRNA are not typically found in the PFC of individuals with depression (Thompson et al, 2009;Sibille et al, 2011), significant decreases in somatostatin suggest that interneuron deficits may be especially prominent in a subset of interneurons shown to directly contribute to cortical plasticity (Lazarus and Huang, 2011). As inhibitory interneuron deficits are shared among those with depression, bipolar disorder, and schizophrenia (Thompson et al, 2009(Thompson et al, , 2011Fung et al, 2010;Hashimoto et al, 2008;Daskalakis et al, 2002), cortical plasticity deficits would also be expected to be found in multiple forms of psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…FS interneurons have a protracted period of postnatal development in primary sensory cortex, reaching an adult-like physiological and anatomical state 3-4 weeks after birth (Okaty et al, 2009;Jiang et al, 2010;Lazarus and Huang, 2011;PangratzFuehrer and Hestrin, 2011). Interestingly, FS3 SP long-term depression (LTD), long-term potentiation (LTP), and spike timing-dependent plasticity are expressed at distinct stages along this postnatal timeline, suggesting that inhibitory plasticity is tuned to interneuron identity and age of the cortex Yazaki-Sugiyama et al, 2009;Lamsa et al, 2010;House et al, 2011;Lefort et al, 2013).…”
Section: Introductionmentioning
confidence: 99%